The Role Of Citizen Journalism In Strengthening Journalistic On The @Lampuung Instagram Account - Fanny Maharani; Noning Verawati; M. Denu Poyo (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the role of citizen journalism in strengthening journalistic practices on the Instagram account @lampuung. Citizen journalism allows the public to actively participate in the collection, dissemination, and verification of information. The @lampuung account, as an example of a social media platform applying the concept of citizen journalism, serves as a channel for distributing information involving direct contributions from the public, such as photos, videos, and narrative reports on various issues. This study uses a qualitative approach with a case study method, collecting data through in- depth interviews with citizen journalists who contribute to @lampuung. The results of the study indicates that citizen journalism on the @lampuung account enhances journalistic practices through three key contributions : accelerating the dissemination of local information, enriching the diversity of perspectives in reporting, and increasing public engagement in the information sharing process. In addition, the role of admin is crucial in maintaining the credibility and validity of the content through layered verification processes. Despite challenges such as low media literacy, technical limitations, and the risk of spreading hoaxes, @lampuung has managed to effectively manage public participation, creating a participatory, adaptive, and responsible digital information ecosystem. This research contributes to the understanding of how social media particularly Instagram can serve as a collaborative space between the public and the media in strengthening local journalistic practices in the era of new media.